Brainstem: Neglected Locus in Neurodegenerative Diseases - Grinberg, Lea T.; Rueb, Udo; Heinsen, Helmut (Frontiers in Neurology, 2011)
The most frequent neurodegenerative diseases (NDs) are Alzheimer’s disease (AD), Parkinson’s disease (PD), and frontotemporal lobar degeneration associated with protein TDP-43 (FTLD-TDP). Neuropathologically, NDs are characterized by abnormal intracellular and extracellular protein deposits and by disease-specific neuronal death. Practically all terminal stages of NDs are clinically associated with dementia. Therefore, major attention was directed to protein deposits and neuron loss in supratentorial (telencephalic) brain regions in the course of NDs. This was also true for PD, although the pathological hallmark of PD is degeneration of pigmented neurons of the brainstem’s substantia nigra. However, PD pathophysiology was explained by dopamine depletion in the telencephalic basal ganglia due to insufficiency and degeneration of the projection neurons located in substantia nigra. In a similar line of argumentation AD- and FTLD-related clinical deficits were exclusively explained by supratentorial allo- and neocortical laminar neuronal necrosis. Recent comprehensive studies in AD and PD early stages found considerable and unexpected involvement of brainstem nuclei, which could have the potential to profoundly change our present concepts on origin, spread, and early clinical diagnosis of these diseases. In contrast with PD and AD, few studies addressed brainstem involvement in the course of the different types of FTLD-TDP. Some of the results, including ours, disclosed a higher and more widespread pathology than anticipated. The present review will focus mainly on the impact of brainstem changes during the course of the most frequent NDs including PD, AD, and FTLD-TDP, with special emphasis on the need for more comprehensive research on FTLDs.